The Use of Choose-Read-Share and Reading Logs as Extensive Reading Strategies to Foster Students' Reading Habits - Dafitri, Fela; Hakim, Putri Kamalia (English Education and Literature Journal (E-Jou), 2025)
Extensive Reading (ER) is a proven approach to enhancing students' reading fluency, comprehension, and motivation. However, many EFL learners struggle with low reading motivation and technology distraction. This study explores the implementation of the Choose-Read-Share (CRS) strategy and Reading Logs to promote extensive reading. Using a qualitative case study approach, data were collected through classroom observations, semi-structured interviews, and document analysis (reading logs). The participants were 17 first-year students of the English Language Education Study Program at Universitas Singaperbangsa Karawang. Thematic analysis was applied to examine their implementation, benefits, and challenges. Findings indicate that CRS and reading logs increased student autonomy and engagement but posed challenges in maintaining motivation and confidence during discussions. While students enjoyed selecting books, some struggled with choosing appropriate materials. The Share stage supported comprehension but caused anxiety for hesitant students. Reading logs were useful for tracking progress but were sometimes seen as burdensome, leading to incomplete entries. Frequent readers showed better comprehension and engagement, supporting Krashen’s Input Hypothesis and the Matthew Effect (Stanovich, 1986). The study concludes that CRS and reading logs are effective but require modifications. Structured peer discussions, flexible reading log formats, and guided book selection are recommended to improve engagement and reduce sharing anxiety.